Anomalous circular bulk photovoltaic effect in BiFeO3 thin films with stripe-domain pattern - David S. Knoche (Nature Portfolio, 2021)
The authors study the evolution of the bulk photovoltaic effect in BiFeO3 thin films with stripe-domains as the polarization of light is modulated from linear to circular. A relationship between the anomalous photo-response and differential light-domain interaction is established.